Sufi Healing Methods For Preventing Anxiety On Patient With Coronary Heart Disease: A Case Study Of Rumah Therapy Haurgeulis, Indramayu, West Java - Erba Rozalina Yanti; Khairunnisa Fitria Permana; Lalu Agus Satriawan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
Patients with coronary heart disease have high anxiety about their future, and most of them cannot accept their current situation. The high level of anxiety happened because of their tendency to avoid their God, so it developed a spiritual emptiness that could affect their psychological condition. Therefore, they were always looking for a solution to minimize their anxiety level to feel inner peace. Until they finally found an alternative medicine based on Sufism(Sufi healing). This research used a qualitative method and was conducted with field research. The respondents who participated in this study were three people between 45-75 years old. Researchers analyzed the process and the impact of the Sufi healing method to quell the anxiety of coronary heart disease patients. In addition, by using comparative descriptive analysis, researchers compare the attitude of respondents before and after the intervention of the Sufi healing method. The results of this method brought significant changes in the level of anxiety and their disease. The clients could control their emotions better; they no longer feel extreme anxiety. They also returned to their daily activities and used their free time to do positive actions, such as reciting Zikr and listening to the Holy Qur’an. These positive activities calmed their inner self and the anxiety at the minimum level to trigger coronary heart disease